Freedom of Religion, Minority Rights and the Law: The Status of Jewish and Muslim Minorities in Europe and Beyond - Gliszczyńska-Grabias, Aleksandra (Taylor & Francis Routledge [Imprint], 2025)
This book provides an in-depth, scholarly reflection on the challenges that arise in guaranteeing religious freedom and protection of the rights of religious minorities in law and practice. Currently, the protection of religious minorities constitutes one of the foundations of the international human rights protection systems and is provided for in the constitutions of all democratic states. The volume identifies, analyses, and assesses the legal status of religious freedom and protection of religious minorities, with special focus on Jewish and Muslim minorities in the European and Israeli legal environments. It compares the discourses on the scope and boundaries of religious freedom with the actual treatment of religious freedom in legal regulations, the case law, and in practice by the general society. The book employs the resources of comparative law and national and international law, as well as legal theory. Extensive use is also made of decisions of the international courts, including the European Court of Human Rights and the Court of Justice of the European Union. The book will be a valuable resource for academics, researchers, and policymakers working in the areas of law and religion, international human rights law, comparative constitutional law, and religious studies